Data Localization in Vietnam: An Introduction of the 2026 Regulatory Framework - Pham Duy Nghia (Universitas Muhammadiyah Surakarta, 2026)
As Vietnam accelerates its digital transformation, the legal framework governing data sovereignty has undergone a significant overhaul. This paper examines the evolution of data localization requirements from the initial Law on Cybersecurity (2018) and Decree 53/2022/ND-CP to the newly implemented Personal Data Protection Law (PDPL) and the Law on Cybersecurity 2025, effective as of early 2026.The study analyzes the specific categories of data subject to local storage-including personal information, user-generated logs, and relationship data-and the conditions under which foreign service providers must establish a local branch or representative office. Furthermore, the paper evaluates the practical challenges faced by multinational corporations in aligning global data strategies with Vietnam's